THE EFFECTS OF DOWNSIZING ON EMPLOYEE COMMITMENT IN THE FREIGHT MANAGEMENT SERVICES IN ZIMBABWE - Mushonga, Tinashe R; Ukpere, Wilfred Isioma (Annals of Spiru Haret University. Economic Series, 2022)
Abstract Downsizing is viewed as a deliberate and systematic organisational reduction of workforce to cut costs and improve performance. There has been ongoing turmoil in the employment relations fraternity for the past few decades, exacerbated by global economic recessions and the need for organisations to adopt new technologies. The effects manifested in organisations’ widespread use and acceptance of downsizing globally. This paper aimed to investigate the untold effects of downsizing on employee commitment in Zimbabwe’s freight management services. Efforts were made to establish implications of the downsizing strategies that organisations in Zimbabwe used, and how employees in freight management services perceived the effects of downsizing on employee commitment. In addition, the present study aimed to identify challenges that employees and organisations faced throughout the downsizing process. The paper adopted a mixed-method research approach. The study found that downsizing was significantly caused by financial crises faced by most organisations in Zimbabwe. Conversely, the results of this study suggested that there was no significant relationship between downsizing and the organisational need to adopt new technologies in Zimbabwe. Interestingly, the study’s findings identified a positive shift in employees’ continuance commitment towards downsizing organisations in Zimbabwe. It was found also that employees remained committed to downsized organisations in Zimbabwe owing to fear of losing their income and a lack of alternative employment. It was also noticed that employees in the freight management services organisations in Zimbabwe suffered detrimental psychological effects such as depression and mental breakdown during and after downsizing. Some recommendations were proffered to reduce the negative effects of downsizing on employees at the Zimbabwe’s freight management services.